Long-term high-dose immunoglobulin successfully treats Long COVID patients with pulmonary, neurologic, and cardiologic symptoms - Thompson, John S.; Thornton, Alice C.; Ainger, Timothy; Garvy, Beth A. (Frontiers in Immunology, 2023)
ABSTRACT Introduction: Long COVID is the overarching name for a wide variety of disorders that may follow the diagnosis of acute SARS-COVID-19 infection and persist for weeks to many months. Nearly every organ system may be affected. Methods: We report 9 patients suffering with Long Covid for 101 to 547 days. All exhibited significant perturbation of their immune systems, but only one was known to be immune deficient prior to the studies directed at evaluating them for possible treatment. Neurological and cardiac symptoms were most common. Based on this data and other evidence suggesting autoimmune reactivity, we planned to treat them for 3 months with long term high dose immunoglobulin therapy. If there was evidence of benefit at 3 months, the regimen was continued. Results: The patient’s ages ranged from 34 to 79 years, 5 males and 4 females. All 9 patients exhibited significant immune perturbations prior to treatment. One patient declined this treatment and insurance support was not approved for two. The other 6 have been treated and all have had a significant to remarkable clinical benefit. Conclusion: Long term high dose immunoglobulin therapy is an effective therapeutic option for treating patients with Long Covid.